2007
DOI: 10.1016/j.nbd.2006.12.008
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 gene deletion prevents neuron loss and memory deficits in 5XFAD APP/PS1 transgenic mice

Abstract: Evidence suggests that β-amyloid (Aβ) peptide triggers a pathogenic cascade leading to neuronal loss in Alzheimer's disease (AD). However, the causal link between Aβ and neuron death in vivo remains unclear since most animal models fail to recapitulate the dramatic cell loss observed in AD. We have recently developed transgenic mice that overexpress human APP and PS1 with five familial AD mutations (5XFAD mice) and exhibit robust neuron death. Here, we demonstrate that genetic deletion of the β-secretase (BACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
218
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(244 citation statements)
references
References 77 publications
14
218
5
1
Order By: Relevance
“…For example, 5XFAD mice exhibit neuron loss and memory deficits that are associated with amyloid pathology (Oakley et al , 2006). Importantly, BACE1 knockout abolishes Aβ deposition in 5XFAD mice and at the same time prevents both memory deficits and neuron loss in this and other mouse models (Ohno et al , 2007). Thus, cerebral Aβ accumulation is responsible for neuron loss and memory deficits in these lines, rather than transgene overexpression, although effects of β‐CTF overexpression cannot be ruled out.…”
Section: Studies On First‐generation Mouse Modelsmentioning
confidence: 68%
“…For example, 5XFAD mice exhibit neuron loss and memory deficits that are associated with amyloid pathology (Oakley et al , 2006). Importantly, BACE1 knockout abolishes Aβ deposition in 5XFAD mice and at the same time prevents both memory deficits and neuron loss in this and other mouse models (Ohno et al , 2007). Thus, cerebral Aβ accumulation is responsible for neuron loss and memory deficits in these lines, rather than transgene overexpression, although effects of β‐CTF overexpression cannot be ruled out.…”
Section: Studies On First‐generation Mouse Modelsmentioning
confidence: 68%
“…First, it is possible that pharmacological approaches with the potent agonist 7,8-DHF may activate BDNF-TrkB signaling more efficiently than gene delivery or stem cell strategies. Furthermore, previous studies from our laboratory and others have demonstrated that elevations in BACE1 have an important role in accelerating disease progression in 5XFAD mouse brains (Devi and Ohno, 2010b;O'Connor et al, 2008;Ohno et al, 2007;Zhang et al, 2009;Zhao et al, 2007) as well as in sporadic AD brains (Fukumoto et al, 2002;Li et al, 2004;Yang et al, 2003).…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies from our laboratory and others have demonstrated that 5XFAD mice recapitulate significant elevations in BACE1 expression (Devi and Ohno, 2010b;Ohno et al, 2007;Zhang et al, 2009;Zhao et al, 2007) reminiscent of sporadic AD brains (Fukumoto et al, 2002;Li et al, 2004;Yang et al, 2003). A two-way ANOVA for BACE1 protein levels revealed significant main effects of genotype (F(1, 24) ¼ 66.38, po0.05) and drug (F(1, 24) ¼ 30.69, po0.05), but not a significant genotype  drug interaction (Figure 5b).…”
Section: Systemic 78-dhf Reduces Bace1 and B-amyloidogenesis In 5xfamentioning
confidence: 88%
See 1 more Smart Citation
“…The amyloid hypothesis is supported by the fact that mutation of APP or presenilins, the catalytic component of  secretase in APP processing, results in more production of A and early onset of familial Alzheimer's disease (FAD) [6,7] . A is found to be toxic in cultured cells and in animal models [8,9] , and inhibition of A production or enhancement of its clearance can attenuate the AD-like pathology [10,11] . The cleavage of APP by secretases is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%